SIMULASI PEMBELAJARAN PENANGANAN KEBAKARAN HUTAN BERBASIS ANDROID - Indra Dharma Wijaya; Ely Setyo Astuti; Arief Prasetyo (SENTIA 2016, 2016)
Simulation-based  learning  android  forest  fire  management  is  the  application  of  learning  media  featuring information in the form of 2D and 3D visualization. Then, the simulation part of the solution wildfires converted into the form of simple games that are intended to attract users. This application is installed on a mobile device with the android operating system. It is intended that the information provided can be accepted easily and can be accessed anywhere and anytime. The aim of this simulation application in order to implement a medium of learning about forests in Indonesia until information regarding forest fires as causes and effects of forest fires and provide treatment when forest fires occur and also solutions forest fires. This app has been tested to some users, including the Forest Service of Malang Regency